2018
DOI: 10.1136/jech-2018-210626
|View full text |Cite
|
Sign up to set email alerts
|

Mental health challenges and experiences in displaced populations following Hurricane Sandy and Hurricane Harvey: the need for more comprehensive interventions in temporary shelters

Abstract: Hurricane exposure can have a profound impact on mental health, leading to increased symptoms of stress, anxiety, depression and post-traumatic stress disorder that are still present years after the storm. Those displaced following a hurricane are particularly vulnerable to adverse mental health outcomes, especially if displaced to temporary shelters. The current work highlights the experiences and mental health challenges of displaced populations following Hurricane Sandy and Hurricane Harvey, as well as desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…Displacement to shelters often results in separation from social support networks and creates a disruption in normal psychological processes, particularly familiarity, attachment and identity, and decrease in perceived social support in the months following the hurricane, which in turn has been shown to be associated with increased symptoms of general psychological distress. Being moved from one shelter to another is traumatic, compounded by the limited amount of healthcare services (91).…”
Section: Airmentioning
confidence: 99%
“…Displacement to shelters often results in separation from social support networks and creates a disruption in normal psychological processes, particularly familiarity, attachment and identity, and decrease in perceived social support in the months following the hurricane, which in turn has been shown to be associated with increased symptoms of general psychological distress. Being moved from one shelter to another is traumatic, compounded by the limited amount of healthcare services (91).…”
Section: Airmentioning
confidence: 99%
“…There is very little research on the relation between Hurricane Harvey and the themes outlined above. Unlike the vast majority of other post‐disaster analyses that entail convenience sampling (see, for example, Zhang et al, ; Schwartz et al, ; Taioli et al, ), the current study participants were initially randomly selected using a probability‐based design for a survey about social vulnerability to flood hazards in summer 2012. Follow up with some of the same set of respondents within 90 days of Harvey enables a pre‐/post‐event study design, which is uncommon among research on disasters (Horney et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the challenging logistics of engaging in social science research on disasters (Taioli et al, ), the more commonly employed ‘after‐only’ study designs habitually appraise people at shelters and community centres. These people have been most affected and may have the fewest resources with which to respond.…”
Section: Introductionmentioning
confidence: 99%
“…20 Another study found that many persons who relocated to shelters after Harvey had high levels of anxiety as a result. 21 A survey of 41 persons in the Houston MSA found that hurricane exposure and property damage were associated with increased symptoms of PTS. 22 Although these studies identified health effects resulting from Harvey, they were not based on representative, population-based samples but instead were based on convenience samples.…”
mentioning
confidence: 99%